Torsin ATPases: structural insights and functional perspectives. (June 2016) - Laudermilch, Ethan; Schlieker, Christian
Abstract : Torsin ATPases are the only members of the AAA+ ATPase family that localize to the endoplasmic reticulum and contiguous perinuclear space. Accordingly, they are well positioned to perform essential work in these compartments, but their precise functions remain elusive. Recent studies have deciphered an unusual ATPase activation mechanism relying on Torsin-associated transmembrane cofactors, LAP1 or LULL1. These findings profoundly change our molecular view of the Torsin machinery and rationalize several human mutations in TorsinA or LAP1 leading to congenital disorders, symptoms of which have recently been recapitulated in mouse models. Here, we review these recent advances in the Torsin field and discuss the most pressing questions in relation to nuclear envelope dynamics.